Dimensionamento de uma edificação residencial unifamiliar em light steel framing - Sufiatti, Larissa da Rosa (2025)
With the aim of presenting the stages of the construction process in Light Steel Framing, this research focuses on the structural sizing of a single-family residential building using this construction system. The study is based on an existing structural design originally conceived in reinforced concrete. Additionally, the research highlights the advantages and disadvantages of this construction method. To achieve this, a literature review was conducted covering the construction system, its components, and the stages of the structural sizing process. The structural analysis and design were carried out using the SCIA Engineer 22.1 finite element 3D software, which operates in compliance with Brazilian standards (ABNT NBR). The main results include the structural sizing of a Light Steel Framing residence and the identification of the structure’s primary deformations.